Ginkgo biloba for acute ischaemic stroke - Zeng, Xianrong (Cochrane Database Syst Rev, 2005)
BACKGROUND: Ginkgo biloba extract is widely used in the treatment of acute ischaemic stroke in China. We aimed to assess the evidence from randomised controlled trials and quasi‐randomised controlled trials on the use of Ginkgo biloba extract in acute ischaemic stroke. OBJECTIVES: The primary objective was to determine whether Ginkgo biloba extract improves functional outcome without causing undue harm in patients with acute ischaemic stroke. Secondary objectives were to assess the effect of Ginkgo biloba extract on neurological impairment and quality of life. SEARCH METHODS: We searched the Cochrane Stroke Group Trials Register (last searched October 2004), the Trials Register of the Cochrane Complementary Medicine Field (last searched October 2004) and the Chinese Stroke Trials Register (last searched June 2004). In addition, we searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library Issue 3, 2004), MEDLINE (1966 to August 2004), EMBASE (1980 to June 2004), AMED (1985 to May 2002) and the China Biological Medicine Database (CBM‐disc, 1979 to August 2004). We searched relevant clinical trials and research registers and contacted pharmaceutical companies and researchers in an effort to identify further published and unpublished studies. SELECTION CRITERIA: Randomised controlled trials or quasi‐randomised controlled clinical trials comparing Ginkgo biloba extract with placebo or open control (no placebo) in patients with acute ischaemic stroke. DATA COLLECTION AND ANALYSIS: Two reviewers independently selected trials for inclusion, assessed trial quality and extracted the data. MAIN RESULTS: Fourteen trials were identified, of which 10 trials (792 patients) were included. Four trials are awaiting assessment. In the 10 included trials follow up was performed at 14 to 35 days after stroke. In all studies neurological outcome was assessed but none of them reported on disability (activities of daily living function) or quality of life. Only three trials reported adverse events. In nine trials, all of them assessed to be of inferior quality, significant improvement in neurological deficit at the end of the treatment was used as the outcome measure. When analysing these trials together, Ginkgo biloba extract was associated with a significant increase in the number of improved patients (Peto odds ratio (OR) 2.66; 95% confidence interval (CI) 1.79 to 3.94). One placebo‐controlled trial, assessed to be of good quality, reported neurological outcome as a continuous variable. It failed to show an improvement of neurological deficit at the end of treatment (weighted mean difference (fixed) 0.81; 95% CI ‐8.9 to 10.52). No deaths or major adverse events were reported during the follow‐up period. AUTHORS' CONCLUSIONS: There was no convincing evidence from trials of sufficient methodological quality to support the routine use of Ginkgo biloba extract to promote recovery after stroke. High‐quality and large‐scale randomised controlled trials are needed to test its efficacy.